Running performance during weekly micro cycles including 2 and 3 matches in elite young soccer players - Komsis, T.; Komsis, S.; Komsis, G.; Dimitrios, P.; Papadopoulou, Z.; Metaxas, T.; Gissis, I.; Vrabas, S. I. (Journal of Physical Education and Sport, 2022)
Despite the fact that a soccer match is very demanding for players body there is extra load with the frequency of matches. The studies had proven that professional soccer players play 1 match per 4.3 days including traveling time. (Kellmann M., 2002).The propose of this study was to record and compare the differences at running performance between two-matches and three-matches in season micro cycles included trainings in order to provide guidelines and information for better management of competition and training load. Ten (n=10) elite youth soccer players of a professional club who participated at Superleague Greece (1st Division) U19 League and Youth League (European u19 championship) with age 18,7±0,67(y), height 1,78±0,4 (m), body weight 69,39±4,16 (kg) and fat tissue 6,74±1,52 (%) constituted the sample of the study. Running performance of each player recorded in all trainings and matches using global position system (GPS) (Viper pod 2, STATSports, Belfast, UK). GPS variables which were selected for analysis included Total Distance (TD), Sprint Distance (SD) vel. >25km/h, High-Speed Running (HSR) vel. > 19,8 km/h, High Metabolic Load Distance (HMLD), Number of Accelerations (Acc) vel. > 3m/s2 and Number of Decelerations (Dec) vel. > 3m/s2. Data from training sessions and matches were collected from two different 7-day periods during Superleague Greece U19 season 2019-2020. Statistical analysis was conducted using SPSS for Windows 15.0 (IBM Corp.). Data were tested with repeated measures analysis and there was significant interaction for Total Distance (TD) with p= ,000 and F= 73,036 also for Number of Decelerations (Dec) with p= ,036 and F= 6,100. In these two variables we continue with paired t test between this two different in season micro cycles. The data analysis showed that two-matches micro cycle had more total distance and decelerations for the players than three-matches micro cycle. These findings reflect the importance of training impact on the players in in-season micro cycles where performance is the main target.